Infant Feeding Practices and Nut Allergy over Time in Australian School Entrant Children - Jessica Paton; Marjan Kljakovic; Karen Ciszek; Pauline Ding (International Journal of Pediatrics)
Aim. To measure the association between infant feeding practices and parent-reported nut allergy in school entrant children. Method. The Kindergarten Health Check Questionnaire was delivered to all 110 Australian Capital Territory (ACT) primary schools between 2006 and 2009. Retrospective analyses were undertaken of the data collected from the kindergarten population. Results. Of 15142 children a strong allergic reaction to peanuts and other nuts was reported in 487 (3.2%) and 307 (3.9%), children, respectively. There was a positive association between parent reported nut allergy and breast feeding (OR=1.53; 1.11–2.11) and having a regular general practitioner (GP) (OR=1.42; 1.05–1.92). A protective effect was found in children who were fed foods other than breast milk in the first six months (OR=0.71; 0.60–0.84). Conclusion. Children were at an increased risk of developing a parent-reported nut allergy if they were breast fed in the first six months of life.